Gratitude as a Mediator between Self-Efficacy and Prosocial Behavior: Implications for Teacher Education Management - Dalimunthe, Hairul Anwar; Partino, Raden; M. Suud, Fitriah; Bashori, Khoruddin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyze the mediating role of gratitude in the relationship between self-efficacy and prosocial behavior, and to examine its implications for teacher education management in Indonesia. Teachers’ prosocial behavior plays a vital role in creating a caring, collaborative, and conducive school climate. While self-efficacy is believed to encourage teachers’ involvement in altruistic actions, the psychological mechanism linking self-efficacy and prosocial behavior through gratitude remains underexplored, particularly in collectivist and religious contexts such as Indonesia. This research employed a cross-sectional quantitative survey design. Self-efficacy, gratitude, and prosocial behavior were measured using standardized Likert-type scales administered to in-service teachers, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The analysis followed two main stages: (1) evaluation of the measurement model to test reliability as well as convergent and discriminant validity, and (2) evaluation of the structural model to estimate path coefficients, explained variance (R²), effect sizes, and indirect effects using bootstrapping procedures. The findings provide significant evidence for the crucial mediating role of gratitude in linking self-efficacy to prosocial behavior. Teachers with high self-efficacy are more likely to engage in prosocial actions, both directly and through the internalization of appreciation.